2020
DOI: 10.13106/jafeb.2020.vol7.no8.117
|View full text |Cite
|
Sign up to set email alerts
|

How Indonesia Economics Works: Correlation Analysis of Macroeconomics in 2010 - 2019

Abstract: The purpose of this study is to provide benefits and ethically-rooted managerial implications based on theoretical underpinnings through an empirical study using correlation between wages, bank credit, government expenditure on economic growth, and employment via a case study in Indonesia. Besides that, managerial implications strive to provide benefits to the government regarding the importance of establishing effective and pro-development regulations to realize economic growth and employment through the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
(115 reference statements)
0
7
0
2
Order By: Relevance
“…This finding is clearly inconsistent with the conclusions drawn by Blejer and Guerrero (1990), Glomm and Ravikumar (1992), Jha (1998) and Afonso et al (2010) who maintain that government investment is the main factor in lowering income inequality. Our finding indicates that local government investment in infrastructure does not provide benefits to increase public economic activity and also does not have an effect on many residents with respect to production activities, which potentially increase income (Olilingo & Putra, 2020). Consequently, government investment does not reduce income inequality.…”
Section: Discussionmentioning
confidence: 64%
“…This finding is clearly inconsistent with the conclusions drawn by Blejer and Guerrero (1990), Glomm and Ravikumar (1992), Jha (1998) and Afonso et al (2010) who maintain that government investment is the main factor in lowering income inequality. Our finding indicates that local government investment in infrastructure does not provide benefits to increase public economic activity and also does not have an effect on many residents with respect to production activities, which potentially increase income (Olilingo & Putra, 2020). Consequently, government investment does not reduce income inequality.…”
Section: Discussionmentioning
confidence: 64%
“…This paper looks at the direct effect of variables on economic growth and it did not examine the threshold level for debt in Malaysia. On the contrary, a study by Olilingo and Putra (2020) found government expenditure has a positive correlation with economic growth.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Still, the APBN/APBD is not understood as an ideological instrument to bring the state's goals closer as a constitutional mandate. The macroeconomic assumptions made are based on narrow goals but ignore the spirit of social justice, such as aspects of income inequality (Olilingo & Putra, 2020;Laurens & Putra, 2020).…”
Section: Introductionmentioning
confidence: 99%